Species delimitation and the origin of populations in island representatives of Phylica (Rhamnaceae) (2007)
Relationships between the closely related island species of Phylica (Rhamnaceae) and a mainland species,P. paniculata, were elucidated using ampli?ed fragment length polymorphisms (AFLPs). Parsimony, neighbor joining,and principal coordinate (PCO) analyses indicated that each of the species studied is distinct. AFLPs were also usefulin elucidating the genetic relationships and possible infraspeci?c origins of different island populations in the Atlanticand Indian Oceans. Phylica nitida on Re´union is likely to have been derived from P. nitida on Mauritius. Althoughthe sampling on New Amsterdam is not extensive, the data are also consistent with the hypothesis that P. arborea onNew Amsterdam was derived from a single colonization of P. arborea from Gough Island. Similarly, the Gough Islandpopulation appears to have been derived from a single colonization event, but it is so distinct from those on Tristanda Cunha, that there may have been two separate dispersals to Gough and Tristan/Nightingale from different lines ofthe mainland progenitor. There is also evidence of a recolonization from Gough to Tristan da Cunha. Thus, Phylicaarborea is capable of repeated long distance dispersal, up to 8000 km, even though the fruits and seeds are not of atype normally associated with this phenomenon.